2017
DOI: 10.1177/0003122417747290
|View full text |Cite
|
Sign up to set email alerts
|

The Roots of Reciprocity: Gratitude and Reputation in Generalized Exchange Systems

Abstract: A drive-through customer pays for the order of the next customer in line, sparking a cascade of nearly 400 customers paying it forward (Phippen 2014). A farmer helps build a neighbor's barn without payment, confident that neighbors will help him when the need arises, a tradition with roots in colonial America and still practiced in Amish and Mennonite communities (Kadushin 2012). A prisoner shares his drugs with fellow inmates, not knowing whether or when they will reciprocate (Mjåland 2014). A researcher agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 61 publications
3
57
0
4
Order By: Relevance
“…This study empirically supports the notion that envy can trigger both constructive reciprocity (Hofmann et al, 2009;Lee & Duffy, 2019) and destructive tactics that undermine others (Puranik et al, 2019;Reh et al, 2018). Benign envy appears less intuitive because the extending of social support and help can be acts of reciprocity and gratitude (Algoe et al, 2019;Simpson et al, 2018) 2011). Since envy is an emotion that triggers behaviour (Lange & Crusius, 2015), envy and prosocial behaviour are not mutually exclusive.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This study empirically supports the notion that envy can trigger both constructive reciprocity (Hofmann et al, 2009;Lee & Duffy, 2019) and destructive tactics that undermine others (Puranik et al, 2019;Reh et al, 2018). Benign envy appears less intuitive because the extending of social support and help can be acts of reciprocity and gratitude (Algoe et al, 2019;Simpson et al, 2018) 2011). Since envy is an emotion that triggers behaviour (Lange & Crusius, 2015), envy and prosocial behaviour are not mutually exclusive.…”
Section: Discussionsupporting
confidence: 66%
“…This study empirically supports the notion that envy can trigger both constructive reciprocity (Hofmann et al, ; Lee & Duffy, ) and destructive tactics that undermine others (Puranik et al, ; Reh et al, ). Benign envy appears less intuitive because the extending of social support and help can be acts of reciprocity and gratitude (Algoe et al, ; Simpson et al, ). Yet, the presence of prosocial behaviour does not necessarily indicate the absence of envious sentiments because benign envy motivates reciprocity as envious individuals extend help to envied individuals (Cohen‐Charash & Larson, ; Lange & Crusius, ; Van de Ven et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore simulated others' decisions to isolate the effects of our manipulated factors from each other and from variation in others' giving behaviors. Further, it is difficult to use observational network data to infer the relational bases of prosociality since prosocial behaviors may flow through triads, but without extended time stamps, it is impossible to isolate the mechanism responsible for giving (31).…”
Section: Introductionmentioning
confidence: 99%
“…We investigated direct reciprocity, generalized reciprocity and both phases or "components" of indirect reciprocity, which we will label "reputational giving" (35) and "rewarding reputation" (15). For simplicity, we refer to direct reciprocity, generalized reciprocity, reputational giving, and rewarding reputation as "four forms" of reciprocity, while recognizing that reputational giving and rewarding reputation, although conceptually distinct, are part of the same chain of giving (31). To isolate the effects of each of the four forms of reciprocity on prosociality while enabling them to be embedded with one another, we fully crossed the four forms with three levels or instantiations of each type, yielding a total of 81 conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, any altruistic behaviour can have a modelling function for other club members; hence, it may be noticed and then imitated or reciprocated. Studies have convincingly shown that individuals gear their own social behaviour to perceived norms and codes of conduct (Keizer et al2008) and they tend to reciprocate helpfulness and cooperation perceived in groups or other persons (Simpson et al 2018). Therefore, sometimes a single initial "altruistic investment" in a group suffices to evoke a positive dynamic, resulting in higher collective levels of solidarity and helpfulness over time (Fowler and Christakis 2010).…”
Section: Prosocial Attitudes and Generalized Reciprocitymentioning
confidence: 99%